External and Internal Environmental Analysis of Strategic Management in the Digital Era - Nurjanah Nasution; Tengku Kespandiar; Sugeng Karyadi; Siera Syailendra; Dian Meliantari (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
Digital micro, small, and medium enterprises are micro, small, and medium enterprises that adopt digital technology in their operations, such as online sales through e-commerce, social media promotions, digital payments like QRIS and e-wallets, and digital business management. This technology aims to expand market reach, improve efficiency, competitiveness, and business growth in the digital economy era. This program is supported by national programs such as micro, small, and medium enterprises go digital. The purpose of this study is to analyze the external and internal environmental of strategic management in the digital era in small, micro, and medium enterprises. This research uses a qualitative approach with a systematic literature analysis using secondary data such as books, journals, and other related sources. The research shows that small, micro, and medium enterprises in the digital era dynamically formulate adaptive strategies based on the internal environmental, such as strengths, weaknesses, resources, and culture, as well as the external environmental, such as opportunities, threats, technological trends, and competitors. The digital era is transforming the way small, micro, and medium enterprises interact, conduct business, and create new business models that leverage data and connectivity for competitive advantage.